Assessing Naira Devaluation and Tight Monetary Policy Impact on Small Medium Enterprises in Nigeria - ABANG, Samuel Oweh; NWANNE, Daniella Chinyere; AMAONYE, Chinenye Blessing; SAMUEL, Loveth Ifeoma Abang (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:This study aims to optimize the management of Munggu Tourist Village through the application of the Business Model Canvas (BMC). By utilizing the BMC framework, tourist village development can become more focused, professional, and sustainable, thereby delivering positive impacts for both tourists and local communities.Methodology:This research employs a qualitative approach. Data collection is conducted through observation, in-depth interviews, and Focus Group Discussions (FGD). In-depth interviews are conducted with business managers in Desa Munggu. The FGD involves inviting the Village Head (Perbekel), the Traditional Village Head (Bendesa Adat Munggu), the Village Supervisory Board, the Chairperson of the Desa Munggu Tourism Awareness Group (Kelompok Sadar Wisata), the Chairperson of the Desa Munggu Tourism Business Management, and the Village Environmental Chairperson.Findings:This finding confirms that the Business Model Canvas (BMC) can serve as a flexible and relevant strategic tool to support the sustainable development of tourism villages based on local wisdom.Implication:This study confirms that the Business Model Canvas (BMC) is a strategic tool that effectively supports the sustainable development of tourism villages based on local wisdom. The findings provide practical guidance for tourism village managers and government authorities in designing effective business strategies, empowering local communities, and maintaining the attractions of the destination. Furthermore, this research encourages responsible tourism management to preserve culture and the environment while opening opportunities for further studies in other tourism destinations.